2015
DOI: 10.1093/carcin/bgv027
|View full text |Cite
|
Sign up to set email alerts
|

miR-29c suppresses pancreatic cancer liver metastasis in an orthotopic implantation model in nude mice and affects survival in pancreatic cancer patients

Abstract: We investigated mechanisms of pancreatic cancer metastasis and defined the biological role of miR-29c in pancreatic cancer metastasis. After two rounds of cell selection in vivo, pancreatic cancer cells with various metastatic potentials derived from spontaneous liver metastases were used as a model of pancreatic cancer to determine the role of miR-29c in pancreatic cancer metastasis. Pancreatic cancer samples were analyzed for miRNA-29c expression, and these levels were associated with survival between groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…1D). To confirm these results, we chose to investigate Hs 766T (the parent cell), Hs 766T-L1, Hs 766T-L2 and Hs 766T-L3 (the daughter cell) cells (Hs 766T-L1, Hs 766T-L2 and Hs 766T-L3 cells are the first, second and third-generation primary tumor cells with increasing invasive ability and derived from a liver metastasis of Hs 766T cells, respectively) [25][26][27]; as the malignancy of PDAC cells increased, the expression levels of miR-222 also increased successively (Fig. 1E).…”
Section: The Identification Of Mir-222 In Pdac Exosomesmentioning
confidence: 99%
“…1D). To confirm these results, we chose to investigate Hs 766T (the parent cell), Hs 766T-L1, Hs 766T-L2 and Hs 766T-L3 (the daughter cell) cells (Hs 766T-L1, Hs 766T-L2 and Hs 766T-L3 cells are the first, second and third-generation primary tumor cells with increasing invasive ability and derived from a liver metastasis of Hs 766T cells, respectively) [25][26][27]; as the malignancy of PDAC cells increased, the expression levels of miR-222 also increased successively (Fig. 1E).…”
Section: The Identification Of Mir-222 In Pdac Exosomesmentioning
confidence: 99%
“…Restored expression of downregulated miRNAs has been suggested to be beneficial in therapeutically targeting cancer [3436]. We and others have recently found miR-29 to be downregulated in PDAC [3739]. Of importance, overexpression of miR-29 in stromal cells reduced the accumulation of stromal proteins and cancer colony formation in direct co-cultures [39].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, by combining fluorescence technique and histological examination, we have demonstrated that our transplantation procedure preserves the mouse cervical cancer microenvironment in such a way that clinically relevant and tumor typeYspecific tumorYlymph node interactions may occur. 19,20 Although the present animal model is a powerful tool for the study of lymph nodes metastasis of cervical cancer, there are also several limitations that could influence the detection of fluorescent tumor cells in vivo. First, as observed in our studies, small, deep lesions will not be detected as a result of the signal being scattered over too wide and too deep of an area.…”
Section: Discussionmentioning
confidence: 99%